Cyclic loading test for interior precast SRC beam-column joints with and without slab. (1st March 2019) - Gao, Qin; Li, Jun-Hua; Qiu, Zhe-Jun; Hwang, Hyeon-Jong
Highlights: A new precast SRC beam-column joints with and without RC slab is designed. Plastic hinge and local buckling of steel beam flanges occurred within the length of the steel beam bracket. Shear studs close to the precast connection cause the delamination between slab and steel beam. The friction coefficient of bolt-connection under cyclic loading is less than that under static loading. Abstract: For better constructability, precast joint segments are used in Steel Reinforced Concrete (SRC) beam-column joints. In this study, quasi-static cyclic tests were performed on six precast SRC beam-column joint specimens with or without slab and one monolithic joint specimen with slab to investigate the load-carrying capacity, deformation capacity, failure mode, stiffness degradation, and energy dissipation capacity. For the test parameters, three connection types of weld-connection, high strength bolt-connection, and a combination of weld- and high strength bolt-connections were considered. The connection location was kept away from the column face so as to avoid the inherent plastic hinge at the connection. The test results showed that the precast SRC beam-column joints with slab exhibited better seismic performance than that of the precast joints without slab. The plastic hinge occurred in steel beam brackets without connection failure. The peak strength was not decreased by bolt-slip at the connection in the joint specimen without slab, while bolt-slip decreased the peak strength of the joint specimen with slab. This study results give an insight to structural engineers for design of precast SRC beam-column joints.